Transferring results of occupational safety and health cost-effectiveness studies from one country to another - a case study - Jos Verbeek; Marjo Pulliainen; Eila Kankaanpää; Simo Taimela (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: There are a limited number of studies about the cost-effectiveness of occupational health and safety (OSH) interventions. Applying the results of a cost-effectiveness study from one country to another is hampered by differences in the organization of healthcare and social security. In order to find out how these problems can be overcome, we transferred the results of a Dutch occupational cost-effectiveness study to the Finnish situation and vice-versa. METHODS: We recalculated incremental cost-effectiveness ratios (ICER) for the target country based on resource use in the original study and the associated costs in the target country. We also allocated the costs to the employer, the employee, and tax-payers. RESULTS: We found that the ICER did not differ very much from those in the original studies. However, the different healthcare funding structure led to a more unfavorable ICER for employers in the Netherlands. Both interventions represented a cost saving for tax-payers and employees. Employers had to invest €10-54 to avert one day of sick leave. CONCLUSIONS: We conclude that results of cost-effectiveness studies can be transferred from one country to another, but many adjustments are needed. An extensive description of the intervention, a detailed list of resource use, allocation of costs to various parties, and detailed knowledge of the healthcare systems in the original studies are necessary to enable calculations.